Ablate and his bundle pace. Issue 3 (March 2018) - Sela, Ron; Kalfon, Eli; Atar, Shaul
Abstract: Atrioventricular junction (AVJ) ablation and pacing therapy is a safe and effective method to control heart rate in patients with atrial fibrillation and rapid ventricular rates who have failed pharmacologic rate control therapies. Usually, the pacing lead of the pacemaker is located at the right ventricular apex or septum, and sometimes the patient has a cardiac resynchronization therapy device with an additional lead implanted through the coronary sinus for left ventricular pacing. We present a 72-year-old woman with permanent atrial fibrillation who developed tachycardia-induced cardiomyopathy. She underwent AVJ ablation following pacemaker implantation with a single lead located at the His bundle region resulting in significant clinical and hemodynamic improvement at follow-up. <Learning objective: We present a case report of a 72-year-old woman with permanent atrial fibrillation who developed tachycardia-induced cardiomyopathy. She underwent atrioventricular junction ablation following pacemaker implantation with a single lead located at the His bundle region, as an alternative to the standard right ventricular apical pacing, with significant clinical and hemodynamic improvement at follow-up.>